Use of bispectral index to monitor depth of anesthesia in isoflurane-anesthetized dogs - Campagnol, Daniela; Teixeira Neto, Francisco José [UNESP]; Monteiro, Eduardo R.; Beier, Suzane L.; Aguiar, Antonio J. A. (Amer Veterinary Medical Assoc, 2007)
Objective-To evaluate the correlation between the bispectral index (BIS) and end-tidal isoflurane (ETISO) concentration and compare the use of 3 BIS sensor positions in dogs.Animals-6 adult dogs.Procedures-Mechanically ventilated dogs received pancuronium, and depth of anesthesia was altered by increasing ETISO concentration from 1.5% to 2.3% and 3.0%. The BIS, suppression ratio (relative percentage of isoelectric electroencephalographic waveforms), and signal quality index (SQI) were recorded at each ET, so concentration for each of 3 BIS sensor positions (frontal-occipital, bifrontal, and frontal-temporal positions).Results-The BIS and ETISO concentration were poorly correlated-, regardless of sensor positioning, mean BIS values did not change significantly as ETISO was increased. At 3% isoflurane, regardless of sensor positioning, there was an increase in suppression ratio coincident with BIS < 40 in some dogs, whereas paradoxic increases in BIS (> 60) were recorded in others. Furthermore, at 3.0% isoflurane, the SQI was significantly lower for the bifrontal sensor position (compared with values for the other positions), but low SQI values prevented recording of BIS values from the frontal-occipital sensor position in 2 dogs. Overall, BIS values derived from the 3 sensor positions did not differ.Conclusions and Clinical Relevance-In dogs, BIS values may not reflect changes in depth of isoflurane anesthesia in the absence of noxious stimulation. of the 3 sensor positions, frontal-temporal positioning provided better correlation with changes in depth of anesthesia induced via changes in isoflurane concentrations. However, the sensor placements yielded similar results at SQI values > 50.